Perancangan Media Pembelajaran Game Edukasi untuk Anak Berkebutuhan Khusus (ABK) Dengan Menggunakan Scratch Anak Autis Ringan di Sekolah Luar Biasa (SLB) Amanah Bunda - Putri, Elsi Kumala; Efriyanti , Liza; Okra, Riri; Musril, Hari Antoni (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
Education is an important part in signaling the progress of a country, especially for a developingcountry, namely Indonesia. Education aims to improve intellectuals, skills and habits to changeone's attitudes and thoughts in order to create a generation of potential and quality in all aspects of life. For Mild Autistic Children at the Amanah Bunda Special School (SLB), there was a problemwhere the learning media still used the natural surroundings such as grass, took it from the internet and then printed it. The use of media is repeated without any development so that it makes students feel bored, not to mention the erratic mood changes of students. So that the Researchers Design Educational Game Learning Media for Children with Special Needs (ABK) Using Scratch on Mild Autistic Children in Amanah Bunda Special Schools (SLB). The method used in this research is the 4-D (four D) version development method. 4D which consists of define, design, develop, and develop Luther-Sutopo multimedia. The results of the validity test of 2 tests are expert is 0.79 with valid criteria, and the results of the test with 2 practicality examiners with a total of 0.91 with very high criteria, and the results effectiveness test with teachers worth 0.05 who are effective and students have an average value of 0.86. And it can be concluded that this educational game learning media is valid, practical and effective and can be used by mild autistic students.